Analysis of Herbal Products by Thin-Layer Chromatography: A Review - A. MOHAMMAD; S.A. BHAWANI; S. SHARMA (International Journal of Pharma and Bio Sciences, 2010)
The standardized thin-layer chromatographic procedures can be used effectively for the screening analysis as well as quality evaluation of the plant or its derived herbal products. . New approaches in thin-layer chromatography enable analysts to separate and determine useful natural products in complex mixtures of plant products. Various chromatographic systems useful for the identification; separation and quantification of herbal products are reported in this review.